Buffering the effects of peer victimization on adolescent non-suicidal self-injury: The role of self-compassion and family cohesion. (December 2016) - Jiang, Yongqiang; You, Jianing; Hou, Yang; Du, Chao; Lin, Min-Pei; Zheng, Xiaoling; Ma, Congfen
Abstract: Non-suicidal self-injury (NSSI) is a significant behavioral problem among adolescents all over the world. This study examined the longitudinal relationship between peer victimization and NSSI, as well as the buffering effects of self-compassion and family cohesion on this relationship. Data were collected at two time points from 525 secondary school students (226 girls; M age  = 12.97, SD  = 1.02) in China. Results showed that peer victimization (marginally) significantly predicted NSSI over time even after controlling for Wave 1 NSSI. This association was weakened under the condition of high levels of self-compassion. Findings of this study emphasize the buffering effect of self-compassion in the relationship between peer victimization and NSSI, and are informative for prevention and intervention of this behavioral problem.